Case Report: Non-typhoidal Salmonella infections transmitted by reptiles and amphibians - Bernar, Benoît; Gande, Nina; Bernar, Aline; Müller, Thomas; Schönlaub, Jörn (Frontiers in Pediatrics, 2023)
Non-typhoidal Salmonella infections (NTSI) can cause bacterial diarrhea, mostly leading to self-limiting gastroenteritis. However, in at-risk populations, NTSI can have severe complications. As transmission is most commonly foodborne, infection is rare in the breast-or bottle-fed very young. Another route is increasingly implicated, however, in newborns and infants especially: Contact with reptiles and amphibians.We describe infection with Salmonella enterica subsp. enterica ser. Monschaui (S. Monschaui), transmitted from bearded dragons, in a three-week-old boy. His case prompted a review of published instances of reptile-and amphibian-associated salmonellosis (RAAS), summarized here. Association of S. Monschaui infection with exposure to reptiles and amphibians prompted inquiry into household pets. The parents had kept bearded dragons (Pogona sp.), the last of which died two weeks before the patient was born; confirmation of colonization with S. Monschaui was thus precluded.Among 63 reports (~5000 cases) of RAAS or S. Monschaui, 62 appeared between 1995 and2022, 10 were single case reports, and 53 were original articles with ~5000 cases; vectors included turtles, frogs, lizards, and snakes.RAAS is not a new phenomenon, but its incidence recently has risen due to the increased popularity of reptiles and amphibians as non-traditional pets. These animals can carry Salmonella sp. and transmit it to humans, posing a risk particularly to infants and other vulnerable persons. Risk mitigation requires that those bringing such pets into the home be informed of dangers associated with reptile and amphibian contact; that those selling reptiles and amphibians be mandated to inform customers comprehensively may be in order.